Emerging Hydro-Climatic Patterns, Teleconnections and Extreme Events in Changing World at Different Timescales - Agarwal, Ankit; Yuan, Naiming; Cheung, Kevin K.W; Shukla, Roopam (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue is expected to advance our understanding of these emerging patterns, teleconnections, and extreme events in a changing world for more accurate prediction or projection of their changes especially on different spatial-time scales.